Interdisciplinaridade e Trabalho em Grupo em Nefrologia - Nascimento, Rosemeire A. (2013)
The high prevalence of psychopathological symptoms among renal patients, the reduced quality of life that adds to their ensuing actual losses, and the lack of information on their illness and treatment, indicates that health professionals should act on these specific points. By means of a critical analysis of interdisciplinarity vis-à-vis multidisciplinarity and taking advantage of the reach of group work, we propose an intervention, consisting of an opened rotating interdisciplinary group, offered to patients admitted to a Nephrology ward, in order to deal with their different demands. As an example, excerpts from one group session are presented, and the various aspects of the intervention are identified and commented on.